2018
DOI: 10.1101/403535
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paranoid schizophrenia and methamphetamine-induced paranoia are both characterized by a similar LINE-1 partial methylation profile, which is more pronounced in paranoid schizophrenia

Abstract: Background: There is evidence that schizophrenia is a neuro-immune disorder. Genes linked to intragenic LINE-1 methylation show a strong association with immune-associated disorders including psychosis. The aim of this study was to examine LINE-1 methylation patterns in paranoid schizophrenia and methamphetamine-induced paranoia, a model for schizophrenia.Methods: This study recruited 31 patients with paranoid schizophrenia, 94 with methamphetamine-induced paranoia (MIP) and 163 normal controls. LINE-1 methyla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Schizophrenia and MA dependence and MIP share several clinical characteristics, and MIP is frequently considered to be a mechanistic model of schizophrenia (Ikeda, Okahisa et al 2013, Gan, Song et al 2018, Kalayasiri, Kraijak et al 2019, Kalayasiri, Kraijak et al 2019). Dopaminergic signaling in the mesocorticolimbic and nigrostriatal networks has been implicated in schizophrenia and MIP (Hogarth, Manning et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia and MA dependence and MIP share several clinical characteristics, and MIP is frequently considered to be a mechanistic model of schizophrenia (Ikeda, Okahisa et al 2013, Gan, Song et al 2018, Kalayasiri, Kraijak et al 2019, Kalayasiri, Kraijak et al 2019). Dopaminergic signaling in the mesocorticolimbic and nigrostriatal networks has been implicated in schizophrenia and MIP (Hogarth, Manning et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, methamphetamine administration may alter DNA methylation patterns through regulation of DNMT1 mRNA levels (Numachi et al, 2007). Interestingly, a recent clinical study showed that methamphetamine-induced changes in long interspersed element-1 methylation are associated with methamphetamine-induced paranoia and therefore may partially explain the pathophysiology of this type of psychosis (Kalayasiri et al, 2019). Previous preclinical study reported that κ1 opioid receptor (OPRK1) promoter methylation was significantly correlated with the length and frequency of drug use in Chinese male heroin addicts (Ji et al, 2018).…”
Section: Introductionmentioning
confidence: 99%